The Nicotinamide Adenine Dinucleotide Phosphate Oxidase Homologues NOX1 and NOX2/gp91(phox) Mediate Hepatic Fibrosis in Mice - Paik, Yong-Han (2011)
NADPH oxidase (NOX) is a multicomponent enzyme that mediates electron transfer from NADPH to molecular oxygen, which leads to the production of superoxide. NOX2/gp91(phox) is a catalytic subunit of NOX expressed in phagocytic cells. Several homologues of NOX2, including NOX1, have been identified in non-phagocytic cells. We investigated the contributory role of NOX1 and NOX2 in hepatic fibrosis. Hepatic fibrosis was induced in wild-type (WT) mice, NOX1-knockout (NOX1KO) mice, and NOX2-knockout (NOX2KO) mice by either CCl(4) injections or bile duct ligation (BDL). The functional contribution of NOX1 and NOX2 in endogenous liver cells, including hepatic stellate cells (HSCs), and bone marrow (BM) derived cells, including Kupffer cells (KCs), to hepatic reactive oxygen species (ROS) generation and hepatic fibrosis was assessed in vitro and in vivo using NOX1- or NOX2-BM chimeric mice. Hepatic NOX1 and NOX2 mRNA expression was increased in the two experimental mouse models of hepatic fibrosis. While NOX1 was expressed in HSCs but not in KCs, NOX2 was expressed in both HSCs and KCs. Hepatic fibrosis and ROS generation were attenuated in both NOX1KO and NOX2KO mice after CCl(4) or BDL. Liver fibrosis in chimeric mice indicated that NOX1 mediates the profibrogenic effects in endogenous liver cells, while NOX2 mediates the profibrogenic effects in both endogenous liver cells and BM-derived cells. Multiple NOX1 and NOX2 components were upregulated in activated HSCs. Both NOX1- and NOX2-deficient HSCs had decreased ROS generation and failed to upregulate collagen α1(I) and TGF-β in response to angiotensin II. CONCLUSION: Both NOX1 and NOX2 in endogenous liver cells, including HSCs, have an important role in hepatic fibrosis, while NOX2 in BM-derived cells has a lesser role.